Sistem Informasi Perhitungan Penyusutan Aktiva Dengan Metode Saldo Menurun Ganda Berbasis Android Menggunakan Standar ISO 25010 - Ardie Halim Wijaya; Wiyono; Andi Leo; Jessen Laorenza Suwandi (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2025)
The study aims to create an application system that can be used to calculate the amount of depreciation of company assets using the double declining balance method based on Android. The methods used in this study are planning, analysis and application program creation. This Android application is created using the React Native language. The application system created is used to enter user identities, create inventory databases, create customer databases and calculate depreciation using the double declining balance method. The application system developed is designed to facilitate communication between users. The results of the study are an application system with several menus, namely the user identity menu, a menu for creating a list of company assets, a menu for adding company assets and a menu for calculating depreciation. This application was then tested using ISO 25010 to determine whether this software is suitable for use or not. The application system developed can be used to calculate asset depreciation easily, quickly and practically as seen from the results of the questionnaire used with an average result of 79.68%.